Advanced topics in end user computing. - Mahmood, Mo Adam. (IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2004)
Advance Topics in End User Computing features the latest research findings dealing with end user computing concepts, issues, and trends. It provides a forum to both academics and information technology practitioners to advance the practice and understanding of end user computing in organizations. Empirical and theoretical research concerned with all aspects of end user computing including development, utilization and management are included.